Flat and Round Singularity theory - Salarinoghabi, Mostafa (2016)
We propose in this thesis a way to study deformations of plane curves that take into consideration the geometry of the curves as well as their singularities. We deal in details with local phenomena that occur generically in two-parameter families of curves. We obtain information on the inflections and vertices appearing on the deformed curves. We also obtain the configurations of the evolutes of the curves and of their deformations, and apply our results to orthogonal projections of space curves. Finally, we consider the profile (outline, apparent contour) of a smooth surface in the Euclidian 3-space. This is the image of the singular set of an orthogonal projection of the surface. The profile is a plane curve and may have singularities. We study the changes in the geometry of the profile as the direction of projection changes locally in the unit sphere.